Village Potential Mapping Based on Development Village Index (DVI) - Sugiono, Sugiono; Cahyawati, Amanda N.; Swara, Suluh E. (Institute of Research and Community Service, University of Brawijaya, 2020)
The independence of the nation's economy depends very much on empowering the rural economy based on its potential. The purpose of this paper is to find out the potential and economic problems of a village based on the Study of Development Village Index (DVI) as the basis for the analysis of sustainable economic development. Exploratory method is used in this research to understand the value of DVI related to village potential mapping. The first step in progress is to do literature studies on village index building and village economic empowerment. Next activity is a survey to collect data based on 6 measuring variables and 12 indicators from the village ministry. Tepas villages, sub district Kesamben, Blitar is one example of applying rural economic development based on its potential mapping. From result of measurement of economic resilience variable got Economic Index (EI) equal to = 0,665. There are several indicators that need to be improved to improve the village economy such as logistic services, banking and village transportation. It can be concluded that the improvement of economic activity in the future is in the form of increasing the smooth flow of goods and services either through the provision of logistic services and the procurement of rural transportation.